Transition from F-75 to ready-to-use therapeutic food in children with severe acute malnutrition, an observational study in Uganda - Lanyero, Betty (Nutr J, 2017)
BACKGROUND: World Health Organization now recommends the transition from F-75 to ready-to-use therapeutic foods (RUTF) in the management of severe acute malnutrition (SAM). We described the transition from F-75 to RUTF and identified correlates of failed transition. METHODS: We conducted an observational study among children aged 6–59 months treated for SAM at Mulago hospital, Kampala, Uganda. Therapeutic feeding during transition phase was provided by first offering half of the energy requirements from RUTF and the other half from F-75 and then increasing gradually to RUTF as only energy source. The child was considered to have successfully transitioned to RUTF if child was able to gradually consume up to 135 kcal/kg/day of RUTF in the transition phase on first attempt. Failed transition to RUTF included children who failed the acceptance test or those who had progressively reduced RUTF intake during the subsequent days. Failure also included those who developed profuse diarrhoea or vomiting when RUTF was ingested. RESULTS: Among 341 of 400 children that reached the transition period, 65% successfully transitioned from F-75 to RUTF on first attempt while 35% failed. The median (IQR) duration of the transition period was 4 (3–8) days. The age of the child, mid-upper arm circumference, weight-for-height z-score and weight at transition negatively predicted failure. Each month increase in age reflected a 4% lower likelihood of failure (OR 0.96 (95% CI 0.93; 0.99). Children with HIV (OR 2.73, 95% CI 1.27; 5.85) and those rated as severely ill by caregiver (OR 1.16, 95% CI: 1.02; 1.32) were more likely to fail. At the beginning of the rehabilitation phase, the majority (95%) of the children eventually accepted RUTF while only 5% completed rehabilitation in hospital on F-100. CONCLUSION: Transition from F-75 to RUTF for hospitalized children with SAM by gradual increase of RUTF was possible on first attempt in 65% of cases. Younger children, severely wasted, HIV infected and those with severe illness as rated by the caregiver were more likely to fail to transit from F-75 to RUTF on first attempt.